HOW POSITIVE THINKING CAN AFFECT STRESS IN MOMS WHO WORKED DURING PANDEMI CORONA? - Kuswartanti, Dyah Rachman (iora, 2020)
According to National Commission for Women in April-May 2020, it was explained that women work twice as much as men in terms of household work with a duration of more than 3 hours. There are 1 in 3 respondents who reported that reported that their work increased household chores made him experience stress. The purpose of this study was to see between positive thinking and the stress of mothers who worked during the corona pandemic. Researchers used observational methods to see only people who think positive and stressed. The data technique is to use interviews as initial data in finding information and the phenomena raised in this study, which is then conducted literature studies from journals and books related to the theory of positive thinking variables and relevant stress. As well as the scale of positive thinking and stress that will be taken by research subjects or participants to answer the research objectives. The number of samples in this study were 82 mothers who worked during the corona pandemic. The positive thinking scale was developed from Albrecht's (1980) theory obtained by the researcher obtaining a reliability test result of 0.938. While the stress scale developed from the theory of Sarafino (2011) made by researchers obtained a re,liability test result of 0.944. Analysis of research data using the use of Pearson products. Based on the results of the Pearson product moment analysis, the value that has no reference is -0.689 with p = 0.000; p â‰¤ 0.01, which indicates a significant negative between positive thinking and stress from working mothers. The effective contribution of the second variable is shown by the determinant coefficient (R square) of 0.468, which shows that positive thinking affects the stress variable of working mothers, 46.8%.